Fenomena Konten Repost Sebagai Komunikasi Pemasaran Digital Pada Instagram @pstore_batam - Siallagan, Naomi; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
In the current digital era, marketing strategies via social media are very important to reach consumers. The Instagram account @pstore_batam uses repost content, namely resharing content from other users, as part of their marketing strategy. This research aims to analyze marketing communication strategies on the Instagram account @pstore_batam using Kotler & Keller's IMC theory. This research uses a qualitative method with a phenomenological approach. The data collection methods used are observation, documentation and literature study. This research shows that the communication strategy used by Instagram @pstore_batam is interactive marketing, through the repost content produced, the audience has an interest in just seeing @pstore_batam posts. The results of research in the comments column of repost content posts show that there is consumer interaction related to their products, this proves that the repost content strategy is effective in attracting consumer buying interest.